A comparison between the South African "source rules" in relation to income tax and the "permanent establishment rules" as contained in double taxation agreements - Fourie, Leonie (Rhodes University, Faculty of Commerce, Department of Accounting, 2008)
South Africa's right to tax the income of a non-resident is determined in terms of the South African "source rules" established by court decisions in relation to the imposition of tax in terms of the Income Tax Act. Unless a non-resident's income is captured by the South African "source rules" (on the basis that hi slits income is derived from a South African source), South Africa would have no right to tax such income, even if such non-resident creates a permanent establishment in South Africa by performing business activities within South Africa which could be considered essential (but not dominant) in nature. In such scenario the activities performed by the non-resident in South Africa may utilise the natural resources and the infrastructure of South Africa, but the South African fiscus would be deprived of the right to any tax revenues attributable to the income produced partly by such activities within South Africa. The South African "source rules" refer only to the main or dominant activities giving rise to the income for the purpose of determining the source of such income (and accordingly the right to tax such income). On the other hand, the "permanent establishment rules" as set out under the Organisation for Economic Cooperation and Development Model Tax Convention on Income and on Capital refer to all the taxpayer's essential business activities for the purpose of determining whether or not such activities create a pennanent establishment. The result of the narrow nature of the South African "source rules" is that, under certain circumstances, the South African fiscus would not necessarily be granted the right to tax all income produced partly within South Africa. The research demonstrated that incorporating the principles underlying the "pennanent establishment rules" into South African legislation would be a reasonable and logical solution to the problem of detennining the source of income. In so doing, the South African "source rules" would determine the source of income, and consequently South Africa's taxing rights, with reference to the essential business activities giving rise to such income. In such case South Africa would be afforded the right to tax the income of a non-resident in the event that it performs any of its essential business activities within South Africa, albeit not the dominant or main activities giving rise to the income.
Keywords: Income tax -- South Africa; Income tax -- Law and legislation -- South Africa; Double taxation -- South Africa; Business enterprises -- Taxation -- South Africa